2002
DOI: 10.1021/je0102614
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherms of Toluene and Gasoline Vapors on DAY Zeolite

Abstract: The adsorption equilibria of toluene and gasoline vapors on DAY zeolite were measured by a static volumetric method. The equilibrium experiments were conducted at (298.15, 318.15, 338.15, 358.15, and 378.15) K and pressures up to 2.5 kPa for toluene and 7.8 kPa for gasoline. The experimental data obtained were correlated by the Toth and UNILAN models, which are generally used for microporous adsorbents such as zeolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…The volumes of the manifold and adsorption cell in the adsorption system were determined by expansion of helium gas at the experimental temperature. Details of the equipment and the operating procedures used are described in the previous work by Ryu et al 8…”
Section: Methodsmentioning
confidence: 99%
“…The volumes of the manifold and adsorption cell in the adsorption system were determined by expansion of helium gas at the experimental temperature. Details of the equipment and the operating procedures used are described in the previous work by Ryu et al 8…”
Section: Methodsmentioning
confidence: 99%
“…1 Because of its strong volatility, a large amount of gasoline vapor is emitted from tanks into the atmosphere in the operation processes (e.g., storage, transportation, loading, and unloading) used in oil reneries, petrochemical factories, oil depots, oil terminals, and gas stations. 2,3 These emissions lead to a series of direct or indirect harmful effects, such as energy resource wastage and signicant economic loss, increased risk of re accidents, increased environmental pollution and damage to human health. 4,5 Therefore, development of advanced technologies for efficient recovery and removal of gasoline vapor is of great signicance in both environmental and energy sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, much work has been carried out to investigate the adsorption of VOCs on some traditional absorbents, such as activated carbon (AC), silica gel, activated alumina and zeolites. Kim et al (2007) studied the adsorption of toluene on bituminous-based activated carbon, and reported its adsorption capacity to be 3 mmol/g at 298 K. Ryu et al (2002) measured the isotherm of toluene adsorbed on DAY zeolite, and reported that the uptake of toluene on this zeolite was 1.66 mmol/g at 2.25 kPa (at 298 K). In another study, Hoang et al (2005) investigated four kinds of adsorbents, namely, MMA-1-RT, MMS-60, MMS-1-80 and MMS-5-80 for the adsorption of toluene and reported that their equilibrium adsorption capacities towards toluene were 3.…”
Section: Introductionmentioning
confidence: 99%